ÁDEBIYAT SABAQLARĺNDA SHĺǴARMALARDĺ BLUM TAKSONOMIYASĺ TIYKARĺNDA OQĺTĺW - Mambetova, G. (SCIENCE and SOCIETY, 2021)
In this article, the ways of using Blum's taxonomy in teaching Karakalpak literature in schools are studied on the basis of T.Kayipbergenov's "Maman biy afsona".